Revision Total Hip Arthroplasty Combined with Subtrochanteric Shortening Osteotomy: Case Report - Sonohata, Motoki (Bentham Open, 2014)
Revision surgery is one of the most difficult reconstructive challenges facing orthopaedic surgeons; therefore, many new techniques and implants are needed to ensure that such patient can be successfully treated. We report a 66-year old female with a chronic dislocated bipolar hip prosthesis. She underwent a revision total hip arthroplasty combined with V-shaped subtrochanteric shortening osteotomy. This report demonstrates that V-shaped subtrochanteric shortening osteotomy can be used for revision surgery. Nevertheless, this technique is not suitable for all hip revisions, and the indications and various possible procedures and devices should be carefully considered to select the best treatment for each patient. We believe that the current report provides evidence supporting a new technical option for complex cases during revision THA.